Synthesis, characterization, and electrocatalytic and electrical properties of novel ball-type four cyclopentyldisilanoxy-POSS bridged metallophthalocyanines - ÖZKAYA, ALİ RIZA (ROYAL SOC CHEMISTRY, 2009)
The novel ball-type four cyclopentyldisilanoxy-POSS bridged binuclear metallophthalocyanines 4-6 (M = Zn, Co, Cu) were synthesized from the corresponding phthalodinitrile derivative 3 which can be obtained from the reaction of cyclopentyldisilanol-POSS 1 with 4-nitrophthalonitrile 2 in THF in the presence of K2CO3 as the base by nucleophilic substitution of an activated nitro group in an aromatic ring. The structures of the target compounds have been characterized by elemental analysis, UV-Vis, IR, MALDI-TOF mass and H-1-NMR spectroscopy techniques. The catalytic activity of the 5-based catalyst towards oxygen reduction in a fuel cell-similar medium involving carbon support and Nafion (R) was observed to be superior when compared to those of 4- and 6-based catalysts, suggesting clearly that the presence of two cofacial redox-active metal centres in the ball-type structure increases the oxygen binding capability of the metal centre and the tendency for the formation of mu-peroxo species. The effect of heat treatment on the dc electrical conductivity and the impedance spectra of the films of 4 and 5 were also studied. The results showed that there were no considerable effects of heat treatment on the dc conductivity of the film of 4. On the other hand, after the films of 5 were annealed at 448 K in vacuum, the conductivity of the films increased similar to 10(3) times.
Keywords: GAS-SENSING PROPERTIES; COBALT PHTHALOCYANINES; COPPER PHTHALOCYANINE; NONLINEAR ABSORPTION; OXYGEN REDUCTION; PHOTOVOLTAIC PROPERTIES; ZINC PHTHALOCYANINES; THIN-FILMS; METAL-FREE; MONONUCLEAR